A Tool for Diagnosing and Staging Synucleinopathies - Claire Erickson (The Journal of Undergraduate Research, 2016)
Synucleinopathies are neurodegenerative diseases characterized by the abnormal accumulation of α-synuclein protein aggregates in the brain. Parkinson’s Disease, the leading movement disorder and synucleinopathy, encompasses roughly 9 million people worldwide and costs in the United States alone total 25 billion yearly. However, there are no standard diagnostic tests for a biological marker of Parkinson’s, such as a blood test or imaging scan. Difficulty in designing an imaging agent stems from the challenge of crossing the blood brain barrier, binding selectively to authentic lesions, and remaining low risk for human patients. This study aims to create an imaging agent that can detect and stage α-synuclein distribution in vivo (live in the patient) via positron emission tomography. Using immunohistochemical methods, human tissue was stained using a commercially available polyclonal anti-α-synuclein antibody and imaged using a con-focal microscope. Tissue stained with our small molecules tagged with a fluorescent ligand recapitulated the images of the positive control, validating that our molecule bound to the target. Preliminary data have provided promising results of the development of an imaging agent that binds authentically to α-synuclein and has the characteristics necessary to pass the blood brain barrier while remaining safe for human consumption. To continue verification, further testing will be done against Tau and β-amyloid protein to ensure the molecule’s selectivity for α-synuclein. Successful completion of this project will provide an objective diagnostic tool for physicians and patients. This tool will be critical in earlier diagnosis and staging of disease, aiding patients and healthcare providers towards better medical treatment and disease outcome.